2022
DOI: 10.1093/braincomms/fcac332
|View full text |Cite
|
Sign up to set email alerts
|

Sleep slow-wave oscillations trigger seizures in a genetic epilepsy model of Dravet syndrome

Abstract: Sleep is the preferential period when epileptic spike-wave discharges appear in human epileptic patients, including genetic epileptic seizures such as Dravet syndrome with multiple mutations including SCN1A mutation and GABAA receptor γ2 subunit Gabrg2Q390X mutation in patients, which presents more severe epileptic symptoms in female patients than male patients. However, the seizure onset mechanism during sleep still remains unknown. Our previous work has shown that the sleep-like state-dependent homeostatic s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(13 citation statements)
references
References 93 publications
(100 reference statements)
1
12
0
Order By: Relevance
“…One pair of EMG leads were inserted into the trapezius muscles to monitor mouse motor activity such as head movements and staring along with simultaneous videos. EEG/multi-unit recordings in vivo As the methods before 21 , post-surgery mice were continuously monitored for recovery from anesthesia and remained in the animal care facility for at least 5 days or 1 week (normal wake/sleep circadian rhythm) before simultaneous EEG/multiunit activity recordings in vivo, along with epileptic behavior being video-recorded for Racinestage scoring. Two-channel EEG (band filtered at 0.1~100Hz) and one-channel POA multi-unit recordings (band filtered 300-10K Hz) along with one channel EMG(band filtered 10-400Hz) were collected by using two multiClamp 700B amplifiers (total 4 channels and all in currentclamp mode) (Molecular devices Inc., Union City, CA) and Clampex 10 software (Molecular Devices Inc., Union City, CA), and digitized at 20 kHz using a Digidata 1440A.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…One pair of EMG leads were inserted into the trapezius muscles to monitor mouse motor activity such as head movements and staring along with simultaneous videos. EEG/multi-unit recordings in vivo As the methods before 21 , post-surgery mice were continuously monitored for recovery from anesthesia and remained in the animal care facility for at least 5 days or 1 week (normal wake/sleep circadian rhythm) before simultaneous EEG/multiunit activity recordings in vivo, along with epileptic behavior being video-recorded for Racinestage scoring. Two-channel EEG (band filtered at 0.1~100Hz) and one-channel POA multi-unit recordings (band filtered 300-10K Hz) along with one channel EMG(band filtered 10-400Hz) were collected by using two multiClamp 700B amplifiers (total 4 channels and all in currentclamp mode) (Molecular devices Inc., Union City, CA) and Clampex 10 software (Molecular Devices Inc., Union City, CA), and digitized at 20 kHz using a Digidata 1440A.…”
Section: Methodsmentioning
confidence: 99%
“…Using one genetic epilepsy mouse model with a Gabrg2 Q390X mutation in gabaergic receptor γ-subunit in cortical neurons and optogenetic method 21,41 , we found that POA multi-unit activity preceded epileptic activity in the het Gabrg2 Q390X KI mice and the POA neurons were active due to epileptic activity in the het Gabrg2 Q390X KI mice. Further, manipulating of the POA activity triggered or suppressed epilepsy incidence in the het Gabrg2 Q390X KI mice, supporting one operational mechanism that the subcortical POA can trigger or regulate epilepsy incidence in this genetic epilepsy model with implications in memory and cognitive deficits in epileptic patients.…”
mentioning
confidence: 95%
See 2 more Smart Citations
“…4 Using the Gabrg2 þ/Q390X knock-in mouse model, Catron and colleagues evaluated slow wave mechanisms for seizures. 5 This mutation has been identified in a subset of patients with the epileptic Dravet syndrome. While most Dravet syndrome cases involve one of many mutations in Scn1a, the gene encoding the voltage-gated sodium channel Na V 1.1, other mutations have been identified, including this one in Gabrg2, the gene for the gamma subunit of the GABA A receptor.…”
Section: Commentarymentioning
confidence: 99%